2009
DOI: 10.1177/0883073808327827
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Treatment of Rett Syndrome With Folate and Betaine

Abstract: We tested the hypothesis that increasing methyl-group pools might promote transcriptional repression by other methyl-binding proteins or by mutant methyl-CpG-binding protein 2 with altered affinity, ameliorating the clinical features of Rett syndrome. A 12-month, double-blind, placebocontrolled folate-betaine trial enrolled 73 methyl-CpG-binding protein 2 mutation positive female participants meeting consensus criteria for Rett syndrome. Participants were randomized as young (< age 5 years) or old (≥ age 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 16 publications
(28 reference statements)
0
30
0
Order By: Relevance
“…Changes, particularly in behavioral outcome measures, may outlast the drug in an unpredictable manner. The same authors conducted the folate-betaine study, a balanced allocation, parallel RCT, which is the largest and longest RCT to date in RTT [84]. The authors recognized methodological issues in their naltrexone study; accordingly, they altered the design to exclude young participants, who are in a period of rapid change, and selected a longer, parallel design, as opposed to a crossover design.…”
Section: Clinical Trials: Resources Possibilities and Challengesmentioning
confidence: 99%
“…Changes, particularly in behavioral outcome measures, may outlast the drug in an unpredictable manner. The same authors conducted the folate-betaine study, a balanced allocation, parallel RCT, which is the largest and longest RCT to date in RTT [84]. The authors recognized methodological issues in their naltrexone study; accordingly, they altered the design to exclude young participants, who are in a period of rapid change, and selected a longer, parallel design, as opposed to a crossover design.…”
Section: Clinical Trials: Resources Possibilities and Challengesmentioning
confidence: 99%
“…Trials of omega-3 fatty acids have been designed to address increased markers of oxidative stress [91,92,102]. Methyl donors such as folate/betaine, folinic acid, and creatine have been used in trials based on clinical observations (low levels of folate in CSF) as well as knowledge of MeCP2 function (DNA methylation) [80,8284,103]. Some recent and current trials continue to employ a general therapeutic approach targeting mitochondrial function with drugs such as EPI-743 and triheptanoin [81] (ClinicalTrials.gov identifier NCT02696044).…”
Section: Drugs Tested In Rtt Trialsmentioning
confidence: 99%
“…Studies aiming at increasing the available pool of methyl groups through intermediate metabolites such as folic acid and betaine, which are known to be involved in the DNA methylation pathway, in the hope of increasing the degree of methylation of some CpG sites and leading to transcriptional repression either by other methylbinding proteins or by a mutant MeCP2 with altered affinity, have failed to demonstrate improvements in the clinical features of RTT [Glaze et al, 2009]. Recently, reevaluation of MeCP2 genomic binding sites has shown that only a small proportion (6%) of these are located inside CpG islands, suggesting that the primary function of MeCP2 is not to bind methylated promoters for repressing transcription [Yasui et al, 2007].…”
Section: Future Therapeutic Perspectivesmentioning
confidence: 99%